TRAFFIC ACCIDENTS UNDER THE INFLUENCE OF PSYCHOACTIVE SUBSTANCES – A STATISTICAL STUDY - Teodora Kiryakova; Metodi Goshev; Biliana Mileva; Dimitar Nikolov; Atanas Christov; Alexandar Alexandrov (Science & Research)

(untitled)
Introduction: The use of psychoactive substances makes driving a car unsafe, as it puts the driver, passengers and other people who share the road at risk. Many of the accidents and deaths that occur on European roads are caused by people whose performance is impaired by alcohol, illicit drugs and medications, or a combination of these substances. Material and methods: We performed full forensic autopsy, toxicological analysis of blood, urine and internal organ samples, with subsequent analysis of the results. Results: For the period 2011-2017 of all cases investigated in the Department of Forensic medicine and deontology, Sofia, Bulgaria in 520 of them the cause of death was associated with traffic accidents. In 81 of the cases the chemical analysis showed the presence of alcohol and/or illicit drugs. Discussion and conclusions: It is well known that alcohol and illicit drugs impair cognitive and physical abilities. Alcohol was the most commonly recorded psychoactive substance in traffic accidents, followed by marijuana, cocaine, amphetamines and opioids. All of these drugs affect the central nervous system, making driving and psychoactive substance use a life-threatening combination. Understanding the effects of alcohol and different illicit drugs, and the correlations between their use and the risk of traffic accidents are necessary to develop effective public health and law enforcement strategies for prevention and control.